UPAYA GURU KELAS DALAM MENGATASI KESULITAN BELAJAR MATEMATIKA (DISKALKULIA) PADA SISWA KELAS V SDN GUNGGUNG 1 - Rafikatul Arifa; Bella Helliyana Febria; Moh. Ainor Rofiqi (Jurnal Edukasi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract Learning difficulties in mathematics are a common issue faced by elementary school students, particularly in basic arithmetic operations, which can impact academic performance and attitudes towards mathematics in the future. This study aims to examine teachers' efforts to address learning difficulties in mathematics among fifth-grade students, especially those with dyscalculia. The research employs a qualitative approach using a case study method at SDN Gunggung 1, with the fifth-grade homeroom teacher selected as the research subject through purposive sampling. Data were collected through in-depth interviews and analyzed using qualitative descriptive analysis techniques. The results indicate that fifth-grade students experience difficulties in learning mathematics, particularly in multiplication and division, driven by low learning motivation, minimal parental supervision due to work commitments, and reliance on technology that diminishes the habit of memorizing basic concepts. The efforts made by the teacher include strengthening multiplication memorization, implementing heterogeneous group learning, and communicating with parents through home visits. This study concludes that overcoming difficulties in learning mathematics requires effective collaboration between teachers, schools, and parents to create optimal continuity in learning. Keywords: learning difficulties, dyscalculia, efforts of teachers Abstrak Kesulitan belajar matematika merupakan permasalahan yang sering dialami siswa sekolah dasar, khususnya dalam operasi hitung dasar yang dapat berdampak pada prestasi akademik dan sikap terhadap matematika di masa depan. Penelitian ini bertujuan untuk mengkaji upaya guru dalam mengatasi kesulitan belajar matematika pada siswa kelas V, khususnya yang mengalami diskalkulia. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus di SDN Gunggung 1, dengan guru wali kelas V sebagai subjek penelitian yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan teknik analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa siswa kelas V mengalami kesulitan belajar matematika terutama pada operasi perkalian dan pembagian yang disebabkan oleh rendahnya motivasi belajar, minimnya pengawasan orang tua akibat kesibukan kerja, dan ketergantungan pada teknologi yang mengurangi kebiasaan menghafal konsep dasar. Upaya yang dilakukan guru meliputi penguatan hafalan perkalian, penerapan pembelajaran kelompok heterogen, dan komunikasi dengan orang tua melalui kunjungan rumah. Penelitian ini menyimpulkan bahwa keberhasilan mengatasi kesulitan belajar matematika memerlukan kolaborasi efektif antara guru, sekolah, dan orang tua untuk menciptakan kontinuitas pembelajaran yang optimal Kata kunci: kesulitan belajar, diskalkulia, upaya guru